Changes in heart rate variability induced by E-sports activities - Wu, Ti; Lee, Po-Yao; Tu, Jie-An; Wang, Hsin-Huan; Chao, Hsueh-Chin; Chen, Chia-Hsiang; Tu, Jui-Hung (Frontiers in Physiology, 2025)
IntroductionIn recent years, E-sports has emerged as a global competitive sports discipline. However, research in the field of exercise science regarding this burgeoning area remains relatively limited. Within this context, an in-depth exploration of E-sports from an exercise science perspective not only aids in optimizing players’ training and performance but also contributes important theoretical and practical value to the advancement of exercise science. This study investigated the physiological changes in E-sports athletes by measuring Heart Rate Variability (HRV).MethodsA total of 40 male college students (mean age 21.2 ± 2.4 years, mean height 171.8 ± 7.9 cm, and mean weight 70.2 ± 11.5 kg) were recruited. Heart rate data were collected before, during, and after gaming using SCOSCHE heart rate armbands. HRV Analysis 1.1 software was employed to convert heart rate changes into HRV parameters. First, a normality test was conducted to determine the data distribution. Since the data did not meet the assumption of normality, the Friedman test was used to compare pre-, during-, and post-gaming heart rate data. Post hoc comparisons were performed using the Wilcoxon signed-rank test with Bonferroni correction. The significance level was set at α = 0.05.ResultsThe results showed that E-sports gaming significantly affected autonomic nervous system activity. Specifically, pre-game mean heart rate (Mean HR) and low-frequency (LF) power were significantly lower than those measured during and after gaming (p < 0.05), while pre-game mean RR interval (Mean RR) was significantly longer (p < 0.05). Furthermore, pre-game HRV indices [e.g., Standard Deviation of NN intervals (SDNN), Root Mean Square of Successive Differences (RMSSD), Number of NN intervals differing by more than 50 ms (NN50), Percentage of NN50 (pNN50)] and high-frequency (HF) power and LF/HF Ratio were significantly higher than those recorded during and after gaming (p < 0.05).ConclusionE-sports gaming imposes stress and fatigue on HRV-related parameters, heightening sympathetic activity and suppressing parasympathetic function. Although certain indicators exhibited a trend toward recovery during the post-gaming rest period, complete recovery appears to require a longer duration. These findings confirm the utility of HRV as an essential tool for monitoring athletes’ physiological status and underscore the need for effective recovery strategies to mitigate the long-term impact of gaming-related stress.